Intra-arterial thrombolysis for retinal artery occlusion: the Calgary experience. - Pettersen, J; Hill, MD; Demchuk, A; Morrish, W; Hudon, M; Hu, W; Wong, J; Barber, P; Buchan, A (2005)
INTRODUCTION: Retinal artery occlusion represents a medical emergency with poor prognosis for visual recovery. Spontaneous improvement is estimated to occur in less than 15% of central retinal artery occlusion (CRAO) cases and conventional treatments have provided only limited benefit. Intra-arterial thrombolysis has been reported as a potentially efficacious and safe treatment. METHODS: We performed a retrospective chart review of all retinal artery occlusion cases treated with intra-arterial recombinant tissue-type plasminogen activator (rtPA) from January 1998 to May 2004. Patients received Goldmann perimetry visual field testing at a variable interval following the procedure (2 days-2.5 years). Visual acuity (VA) was re-assessed in May 2004. RESULTS: Eight cases (59-77 years) were treated for CRAO, 6-18 hours post-onset with intra-arterial rtPA (10-20 mg over 15-60 minutes); one case of branch occlusion (BRAO) was treated with 30 mg rtPA over 75 minutes, 12 hours post-onset. Among the six patients with CRAO assessed in clinic, three experienced improvement in VA by two or more gradations (Snellen lines); three improved by one gradation. However, none achieved a final VA better than 20/300. The case of branch occlusion improved to a VA of 20/20. All patients had residual monocular field defects. CONCLUSIONS: Our findings reveal a limited benefit for intra-arterial tPA compared to the rate of spontaneous improvement and conventional forms of therapy for retinal artery occlusion.